Analisis Faktor yang Berhubungan dengan Penerapan Budaya Keselamatan Pasien pada Perawat - Dewi Kuraesin; Rina Mutiara; Rokiah Kusumapradja (Jurnal Health Sains, 2023)
Patient safety culture is a product of values, attitudes, competencies and behavioral patterns of individuals and groups that determine the commitment, style and ability of a health care organization towards patient safety programs. if a health service organization does not have a patient safety culture, accidents can occur resulting in latent errors, psychological and physiological disturbances to staff, decreased productivity, reduced patient satisfaction and cause interpersonal conflicts. leadership, competence and effective communication are important factors for the successful implementation of patient safety culture in hospitals. Analyzing the relationship of leadership, competency and effective communication to the implementation of patient safety culture. This research was conducted on 179 nurses working in the inpatient room of the XX Serang hospital which were taken from 323 nurses, with the research method using cross-sectional research, where data was taken through interviews using questionnaire sheets. In this study the authors used statistical analysis of the Cji Square test and correlation test to determine the strength of the relationship between variables. Statistical test results obtained values for leadership variables 0.001, competence 0.000 and effective communication 0.017 < P value (0.05) so that it can be concluded that there is a significant relationship between leadership, competence and effective communication on the application of patient safety culture to nurses in inpatient rooms of XX hospital Attack. While the results of the correlation test obtained a coefficient value for leadership 0.25, competence 0.043 and effective communication 0.164, of the three independent variables, it is the leadership variable that has a higher value than the others, this shows that leadership plays a very high role in implementing patient safety culture to nurses in the inpatient room of the XX Serang Kata hospital